Implementation of PBL-Based Digital Worksheets to Improve Students’ Problem-Solving Skills: A Literature Review - Katarina Sanca; Rahmatta Thoriq Lintangesukmanjaya; Dwikoranto; Neisya Azaria Adinda Putri (Journal of Digitalization in Physics Education, 2026)
Objective: This study aims to analyze previous research on the implementation of Problem-Based Learning (PBL)-based digital worksheets and examine their contribution to improving students’ problem-solving skills, particularly in physics, where conceptual understanding and analytical reasoning are essential. Method: This research employs a literature review, analyzing 20 relevant articles published between 2021 and 2025 that discuss the integration of PBL and digital worksheets in educational contexts. Many studies focus on physics education topics such as motion, hydrostatic pressure, momentum, optical instruments, and global warming. The selected articles were systematically reviewed and synthesized to identify trends, findings, and the effectiveness of PBL-based digital worksheets in supporting students’ problem-solving abilities. Results: The results of the review indicate that PBL-based digital worksheets positively impact students’ problem-solving skills by providing structured activities through problem identification, investigation, analysis, and solution development. In physics education, these worksheets help students understand abstract concepts, connect formulas with real-world phenomena, and solve contextual physics problems more effectively. They also create interactive, student-centered learning environments that foster active participation and higher-order thinking. In addition, this review shows that digital worksheets have evolved from simple task sheets into adaptive learning tools that support feedback, collaboration, and independent learning.  Novelty: The novelty of this study lies in highlighting PBL-based digital worksheets as not only instructional media but also as pedagogical innovation that integrates physics problem-solving processes with digital technology to improve students’ problem-solving skills, conceptual understanding, and digital competence.